First Principles Investigations on the Electronic and Magnetic Properties of La4Ba2Cu2O10 - Bhandari, Shalika Ram; Thapa, Ram Kumar; Ghimire, Madhav Prasad (Journal of Nepal Physical Society, 2016)
Electronic and magnetic properties of La4Ba2Cu2O10 had been studied by first-principles density functional theory (DFT). Based on the DFT calculation La4Ba2Cu2O10 is found to have a ferromagnetic (FM) ground state. The material undergo charge-transfer type insulator to Mott-Hubbard type insulator transition which happens due to strong correlation in La-4f and Cu-3d states. Our results show that the 3d electrons of Cu hybridize strongly with O-2p states near the Fermi level giving rise to the insulating state of La4Ba2Cu2O10. Our study suggests that the enhanced magnetic moment is a result of itinerant exchange rather than the exchange interaction involving individual ions of Cu atoms. The total magnetic moment calculated in the present studies is 2 μB per unit cell for La4Ba2Cu2O10. Journal of Nepal Physical Society Vol.3(1) 2015: 89-96